Home-based records for poor mothers and children in Afghanistan, a cross sectional population based study - Sayed Ataullah Saeedzai; Iftekhar Sadaat; Zelaikha Anwari; Shafiqullah Hemat; Shakir Hadad; Keiko Osaki; Megumi Asaba; Yohei Ishiguro; Rasuli Mudassir; Jane Machlin Burke; Ariel Higgins-Steele; Khaksar Yousufi; et al. (BMC, 2019)
Abstract Background No studies have examined distribution, retention and use of maternal and child health (MCH) home-based records (HBRs) in the poorest women in low income countries. Our primary objective was to compare distribution of the new Afghanistan MCH HBR (the MCH handbook) to the poorest women (quintiles 1-2) with the least poor women (quintiles 3-5). Secondary objectives were to assess distribution, retention and use of the handbook across wealth, education, age and parity strata. Methods This was a population based cross sectional study set in Kama and Mirbachakot districts of Afghanistan from August 2017 to April 2018. Women were eligible to be part of the study if they had a child born in the last 6 months. Multivariable logistic regression models were constructed to adjust for clustering by district and potential confounders decided a priori (maternal education, maternal age, parity, age of child, sex of child) and to calculate adjusted odds ratios (aOR), 95% confidence intervals (95% CI) and corresponding p values. Principal components analysis was used to create the wealth quintiles using standard methods. Wealth categories were 'poorest' (quintiles 1,2) and 'least poor' (quintiles 3,4,5). Results 1728/1943 (88.5%) mothers received a handbook. The poorest women (633, 88.8%) had similar odds of receiving a handbook compared to the least poor (990, 91.7%) (aOR 1.26, 95%CI [0.91-1.77], p value 0.165). Education status (aOR 1.03, 95%CI [0.63-1.68], p value 0.903) and age (aOR 1.39, 95%CI [0.68-2.84], p value 0.369) had little effect. Multiparous women (1371, 91.5%) had a higher odds than primiparous women (252, 85.7%) (aOR 1.83, 95%CI [1.16-2.87], p value 0.009). Use of the handbook by health providers and mothers was similar across quintiles. Ten (0.5%) women reported that they received a book but then lost it. Conclusions We were able to achieve almost universal coverage of our new MCH HBR in our study area in Afghanistan. The handbook will be scaled up over the next three years across all of Afghanistan and will include close monitoring and assessment of coverage and use by all families.